4β‐Hydroxywithanolide E selectively induces oxidative DNA damage for selective killing of oral cancer cells - Tang, Jen‐Yang; Huang, Hurng‐Wern; Wang, Hui‐Ru; Chan, Ya‐Ching; Haung, Jo‐Wen; Shu, Chih‐Wen; Wu, Yang‐Chang; Chang, Hsueh‐Wei (Environmental toxicology, 2018)
Reactive oxygen species (ROS) induction had been previously reported in 4β‐hydroxywithanolide (4βHWE)‐induced selective killing of oral cancer cells, but the mechanism involving ROS and the DNA damage effect remain unclear. This study explores the role of ROS and oxidative DNA damage of 4βHWE in the selective killing of oral cancer cells. Changes in cell viability, morphology, ROS, DNA double strand break (DSB) signaling (γH2AX foci in immunofluorescence and DSB signaling in western blotting), and oxidative DNA damage (8‐oxo‐2′deoxyguanosine [8‐oxodG]) were detected in 4βHWE‐treated oral cancer (Ca9‐22) and/or normal (HGF‐1) cells. 4βHWE decreased cell viability, changed cell morphology and induced ROS generation in oral cancer cells rather than oral normal cells, which were recovered by a free radical scavenger N‐acetylcysteine (NAC). For immunofluorescence, 4βHWE also accumulated more of the DSB marker, γH2AX foci, in oral cancer cells than in oral normal cells. For western blotting, DSB signaling proteins such as γH2AX and MRN complex (MRE11, RAD50, and NBS1) were overexpressed in 4βHWE‐treated oral cancer cells in different concentrations and treatment time. In the formamidopyrimidine‐DNA glycolyase (Fpg)‐based comet assay and 8‐oxodG‐based flow cytometry, the 8‐oxodG expressions were higher in 4βHWE‐treated oral cancer cells than in oral normal cells. All the 4βHWE‐induced DSB and oxidative DNA damage to oral cancer cells were recovered by NAC pretreatment. Taken together, the 4βHWE selectively induced DSB and oxidative DNA damage for the ROS‐mediated selective killing of oral cancer cells.